1991
DOI: 10.1111/j.1432-1033.1991.tb16272.x
|View full text |Cite
|
Sign up to set email alerts
|

The conformation of porcine‐brain natriuretic peptide by two‐dimensional NMR spectroscopy

Abstract: Two-dimensional (2D) 'H-NMR spectra of porcine-brain natriuretic peptide (pBNP) have been recorded at 300 MHz and 400 MHz. Peak assignments have been made and the combined information from chemical shifts, coupling constants, temperature coefficients and NOES have been used to determine the conformational properties of pBNP in (C2H3)2S0. Overall the peptide appears to be flexible, with the possibility of some P-type structure near the C terminus. Some of the assignments and deduced structural features in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…All cysteine residues found to be topologically equivalent by the DALI algorithm were disulphide-bonded in an identical fashion in each molecule. The anti-parallel β-strands in DLP-1 (15)(16)(17)(18)(37)(38)(39)(40) correspond closely with those in β-defensin-12 (10)(11)(12)(13)(32)(33)(34)(35)(36), although one of the strands in the latter is longer by one residue. Part of the large loop in DLP-1, defined by residues 24-27 and 30-36, corresponds to the region in β-defensin-12 defined by residues 21-31, which contains a β-strand and a βbulge.…”
Section: Similarity Of the Overall Fold With β-Defensin-12mentioning
confidence: 76%
See 1 more Smart Citation
“…All cysteine residues found to be topologically equivalent by the DALI algorithm were disulphide-bonded in an identical fashion in each molecule. The anti-parallel β-strands in DLP-1 (15)(16)(17)(18)(37)(38)(39)(40) correspond closely with those in β-defensin-12 (10)(11)(12)(13)(32)(33)(34)(35)(36), although one of the strands in the latter is longer by one residue. Part of the large loop in DLP-1, defined by residues 24-27 and 30-36, corresponds to the region in β-defensin-12 defined by residues 21-31, which contains a β-strand and a βbulge.…”
Section: Similarity Of the Overall Fold With β-Defensin-12mentioning
confidence: 76%
“…The 4.2-kDa peptide, which shares a high degree of sequence identity with human and porcine C-type natriuretic peptide, has relaxant, oedema-producing and mast-cell-degranulating activities [11]. NMR studies of similar natriuretic peptides from various mammals revealed their tertiary structures to be flexible with little indication of well-defined secondary structure [12][13][14]. The other three protein components discovered in platypus venom do not resemble any of the proteins listed in the SwissProt database.…”
Section: Introductionmentioning
confidence: 99%
“…Previous NMR studies of free NP hormones show that they exist in an unstructured form unless rigidified synthetically. 24,25 The implications are that strategies to design mimics of small peptide hormones that exist as highly flexible ensembles of conformations in solution, based on calculations of low energy states, are inherently compromised by the fact that the receptor bound conformation need not be a stable or highly populated state in the unbound conformation. 25 It appears that in the case of the NP, hormone binding is inducing structure in the peptides.…”
Section: B Pairwise Interactions Between Npr-c/cnp and Npr-a/anpmentioning
confidence: 99%
“…All cysteine residues found to be topologically equivalent by the DALI algorithm were disulphide-bonded in an identical fashion in each molecule. The anti-parallel β-strands in DLP-1 (15)(16)(17)(18)(37)(38)(39)(40) correspond closely with those in β-defensin-12 (10)(11)(12)(13)(32)(33)(34)(35)(36), although one of the strands in the latter is longer by one residue. Part of the large loop in DLP-1, defined by residues 24-27 and 30-36, corresponds to the region in β-defensin-12 defined by residues 21-31, which contains a β-strand and a βbulge.…”
Section: Similarity Of the Overall Fold With β-Defensin-12mentioning
confidence: 75%